Poziom lęku i depresji u pacjentów poddanych rehabilitacji sanatoryjnej = The level of anxiety and depression in patients undergoing rehabilitation treatment in a sanatorium - Kocjan, Janusz (Journal of Education, Health and Sport, 2015)
Kocjan Janusz. Poziom lęku i depresji u pacjentów poddanych rehabilitacji sanatoryjnej = The level of anxiety and depression in patients undergoing rehabilitation treatment in a sanatorium. Journal of Education, Health and Sport. 2015;5(5):389-400. ISSN 2391-8306. DOI 10.5281/zenodo.17899 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A373-388 https://pbn.nauka.gov.pl/works/561544 http://dx.doi.org/10.5281/zenodo.17899 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.02.2015. Revised 18.04.2015. Accepted: 25.05.2015. POZIOM LĘKU I DEPRESJI U PACJENTÓW PODDANYCH REHABILITACJI SANATORYJNEJ THE LEVEL OF ANXIETY AND DEPRESSION IN PATIENTS UNDERGOING REHABILITATION TREATMENT IN A SANATORIUM Janusz Kocjan Śląski Uniwersytet Medyczny w Katowicach, Wydział Lekarski w Katowicach Medical University of Silesia, Faculty of Medicine, Katowice, Poland STRESZCZENIE Wstęp: Lęk i depresja powszechnie występują w ogólnej populacji. Wciąż jednak niewiele wiadomo na temat ich obecności oraz nasilenia wśród pacjentów poddanych rehabilitacji sanatoryjnej. Cel pracy: Celem pracy była ocena objawów lęku i depresji w grupie pacjentów poddanych stacjonarnej rehabilitacji sanatoryjnej. Dokonano również oceny zróżnicowania nasilenia lęku i depresji ze względu na płeć, wiek oraz poziom wykształcenia badanych. Materiał i metody: Zbadano 70 osób w wieku od 41 do 80 lat: 36 kobiet (średni wiek: 65,05 ± 8,92 lat) oraz 34 mężczyzn (średni wiek: 64,14 ± 9,89 lat). W badaniu posłużono się Szpitalną Skalą Lęku i Depresji (ang. Hospital Anxiety and Depression Scale, HADS) uzupełnioną kwestionariuszem własnej konstrukcji. Wyniki: Średnie wartości lęku mieściły się w granicach wartości prawidłowych, zarówno u kobiet jak i u mężczyzn - bez istotnych różnic statystycznych ze względu na płeć. W przypadku depresji, nasilenie wykraczające poza granice wartości prawidłowych odnotowano u prawie 60% badanych mężczyzn – w porównaniu do 23,5% zaobserwowanych u kobiet. U mężczyzn wykazano korelacje istotne statystycznie między poziomem wykształcenia a nasileniem objawów lęku i depresji. U kobiet odnotowano istotny statystycznie związek wieku i poziomu wykształcenia ze stopniem prezentowanych objawów lękowych. Wnioski: Płeć, wiek oraz poziom wykształcenia silnie różnicują nasilenie objawów lęku i depresji Słowa kluczowe: lęk, depresja, sanatorium, rehabilitacja. SUMMARY Introduction: Anxiety and depression are common in the general population. However, still is little known about their presence and severity among patients undergoing rehabilitation in a sanatorium. Aim of the study: The aim of the present study was to evaluate symptoms of anxiety and depression in group of patients subjected rehabilitation in a sanatorium. Differentiation of severity of anxiety and depression based on gender, age and education level was also assessed. Material and methods: 70 patients in age of 41-80 years: 36 females (mean age: 65,05 ± 8,92 years) oraz 34 males (mean age: 64,14 ± 9,89 years) participated in this study. HADS (Hospital Anxiety and Depression Scale) and author designed questionnaire were used. Results: The mean values of an anxiety were in the normal points range, both in women and men - but with no statistically significant differences based on gender. In the case of depression, severity beyond the limits of normal points value were reported in nearly 60% of male respondents - compared to the 23.5% observed in women. Statistically significant correlation between education level and the intensity of the symptoms of anxiety and depression were noted in men. In women, reported a significant relationship between age and education level with degree of presented anxiety symptoms. Conclusions: Gender, age and education level strongly differentiate the severity of symptoms of anxiety and depression. Key words: anxiety, depression, sanatorium, rehabilitation.